A study of certain personality, educational and environmental variables associated with science orientation, in a selected group of fifth form students, in secondary schools of Jamaica - Hamilton, Marlene A. (1976)
This study sought to probe the effects of certain variables on science orientation in a select sample of Jamaican boys and girls completing their fifth form year of secondary schooling. Data were collected from a sample of 618 fifth form students (281 male, 337 female; 371 urban, 247 rural) from three types of secondary high schools (government owned or aided, single-sex boys' and girls', co-educational). Students' General Certificate of Education (GCE) O'Level grades were used as the criterion measure. Results of the data analysis revealed: 1) the existence of five factors: a) a "School Environmental Factor" for both male and female Ss; b) a "Scientific Ability Factor" for female Ss only; c) a "Scientific Inclinations Factor" for both groups; d) a "Social Environment Factor" for male Ss, and e) a weakly defined "Personality Factor," displayed only in the case of female Ss; 2) that the best predictors of science orientation were: i) Early Educational Experiences, Space Relations, and Scientific Attitude for female Ss; and ii) Vocational Aspirations, Type of Student, and Abstract Reasoning for male Ss; 3) that there was a sex difference in favour of male Ss on most variables associated with science orientation; 4) that for Ss continuing to sixth form, sciences were the most popular options selected; and 5) that for the practising Jamaican scientist, personality factors made little impact, but certain educational variables, such as Early School Experiences, Intellectual Ability, and Liking for Science were important determinants, positively related to science orientations
Keywords: Secondary school students